‘To Coosen the Expectation’: George Gascoigne’s Moral ‘Poses’ in Supposes - Silvestri, Silvia (Early Theatre, 2024)
Supposes, based on Ludovico Ariosto’s Suppositi, found its way into print twice during George Gascoigne’s lifetime: first, in A Hundreth Sundrie Flowres (1573); then, in The Posies of George Gascoigne, a 1575 revised version of Flowres. In Posies’s prefatory letters, Gascoigne presents the collection as the ‘undoubted proof’ of his reformation, advertising the ‘morall discourses and reformed inventions’ it harbours. Recent criticism questions these claims, arguing for the marginality and inconsistency of Gascoigne's revisions, yet gives little consideration in this respect to the actual works featured in the miscellany, including Supposes – a play rich in sexual innuendos, left unamended in Posies. This article addresses this gap by reconsidering Supposes as functional to Gascoigne’s deceptive fiction of reformation as set forth in Posies’s paratexts.